Elicitation study investigating hand and foot gesture interaction for immersive maps in augmented reality. Issue 3 (3rd May 2020) - Austin, Christopher R.; Ens, Barrett; Satriadi, Kadek Ananta; Jenny, Bernhard
ABSTRACT: Immersive maps in augmented reality (AR) are virtual maps that plausibly blend with the physical environment, such that the user perceives them as a part of the real world. While immersive maps can offer unprecedented engaging experiences, the way to perform panning, zooming and other basic map interaction is not obvious. This limitation may hamper widespread adoption of immersive maps. We therefore conducted an elicitation study to identify commonly suggested hand and foot gestures for interacting with large immersive AR maps placed on the floor. Study participants were shown simulations of interaction operations, and asked to design gestures to trigger these operations. We selected interaction with hand gestures because they are natural and familiar from interacting with touchscreens. Foot gestures were included because the users' feet touch immersive maps placed on the floor. Eighteen participants designed hand and foot gestures for panning, rotating, zooming, changing the height of the map, creating a point marker, and selecting a point marker. The most agreed-on hand gesture was for zooming, consisting of grabbing with both hands, then separating or bringing the hands together. Our study participants suggested numerous other inspirational hand and foot gestures, which can guide the further development of interactive immersive maps. Because user preference does not necessarily align with performance, it is important to evaluate the efficiency, accuracy, ease of learning, and physical fatigue for these gestures in follow-up studies.